Do donors matter most? An analysis of conditional cash transfer adoption in Sub-Saharan Africa. (August 2018) - Simpson, Joshua P
Cash transfers, both conditional and unconditional, have become increasingly popular in emerging economies, but relatively little research investigates the types of countries most likely to adopt this form of social assistance. A notable exception is a study by Brooks, which concludes that conditional cash transfers (CCTs) are more likely to be adopted by divided governments and in places where neighbouring, democratic countries have already implemented them. This comparative research tests Brooks' findings in the context of Sub-Saharan Africa (SSA) and finds that they largely do not apply. Instead, programme funder is offered as a better explanation of cash transfer adoption in SSA from 1990 to 2011. The results show that CCTs are adopted in poor African countries with financial support from the World Bank, while unconditional cash transfers (UCTs) are adopted across a range of countries with the support of various donors. This research contributes to the literature by showing quantitatively that donor support may be more important than some domestic factors, such as bureaucratic capacity, for understanding CCT implementation in SSA.